Muscle metabolism and performance improvement after two training programmes of sprint running differing in rest interval duration - Saraslanidis, P.a , Petridou, A.a , Bogdanis, G.C.b , Galanis, N.c , Tsalis, G.a , Kellis, S.a , Mougios, V.a (Journal of Sports Sciences, 2011)
Repeated-sprint training often involves short sprints separated by inadequate recovery intervals. The effects of interval duration on metabolic and performance parameters are unclear. We compared the effects of two training programmes, differing in rest interval duration, on muscle (vastus lateralis) metabolism and sprint performance. Sixteen men trained three times a week for 8 weeks, each training session comprising 2-3 sets of two 80-m sprints. Sprints were separated by 10 s (n = 8) or 1 min (n = 8). Both training programmes improved performance in the 100-, 200-, and 300-m sprints, but the improvement was greater in the 10-s group during the final 100 m of the 200- and 300-m runs. Independent of interval duration, training mitigated the drop of muscle ATP after two 80-m sprints. The drop in phosphocreatine and the increases in glucose-6-phosphate and fructose-6-phosphate after two 80-m sprints were greater in the 10-s group. In conclusion, training with a limited number of repeated short sprints (≤10 s) may be more effective in improving speed maintenance in 200- and 300-m runs when performed with a 1:1 rather than a 1:6 exercise-to-rest ratio. This may be due to a greater activation of glycolysis caused, in part, by the limited resynthesis of phosphocreatine during the very short rest interval. © 2011 Taylor & Francis.